Influence of maternal level of education and socioeconomic status on maternal knowledge of nutrition, physical activity and children's bodyweight of Nigerian school pupils - Adebisi I. Hammed; Suleiman O. Usman; Onyemechi Ezekiel; Joy C. Duru; Oluwaseun J. Oladimeji; Ogolo Jirho (University of Novi Sad, Faculty of Sport and Physical Education, 2021)
This study investigated the influence of maternal level of education and socioeconomic status on maternal knowledge of nutrition, physical activity, and children's body weight of Nigerian school pupils. A total of four hundred and twelve (412) primary school pupils participated in this study. A structured questionnaire was used to assess the maternal level of education, material's knowledge of nutrition, and physical activities. Body height and body weight were measured with a wall-mounted stadiometer in meters and a bathroom weighing scale in kg, respectively. The children's body weight was determined using the formula weight (kg)/height (m2). The children were then categorized into different classes of body mass index based on the recommendation of Centers for Diseases Control and Prevention (2015), which is age and sex-specific for children and teens from two years old through 20 years. The differences in maternal educational qualification and children's bodyweights were analyzed using the independent sample t-test. However, the influence of maternal SES on maternal knowledge of nutrition, physical activities, and children's body weights were analyzed using ANOVA. Statistical significance was accepted for a p-value of <0.05. The outcome of this study showed that the educational qualification of mothers had a significant (p<0.05) influence on children's bodyweights. It was also observed from this study that the maternal SES significantly (p<0.05) influenced maternal nutritional knowledge, maternal knowledge of physical activities, and children's bodyweights. This study therefore concluded that the maternal level of education and SES do influence maternal knowledge of nutrition and physical activity as well as children's bodyweights.